The use of aloe vera as an adjunct in periodontal treatment (Research, Society and Development, 2021)
Objective: To review the most current studies in the literature on the efficacy of Aloe Vera as an adjuvant in periodontal treatment. Material and Methods: We selected scientific articles published between 2013 and 2019 through the PubMed and Google Scholar databases with the following descriptors in Portuguese and English respectively, “Gingivitis (Gengivitis)”, “Periodontitis (Periodontitis)”, “Aloe (Aloe)”, “Phytotherapeutic Drugs”, “Periodontics (Periodontics)” and “Dentistry (Dentistry), chosen by consulting the BIREME Health Sciences Descriptors - DECs. Results: Aloe Vera is a medicinal plant with actions similar to chlorhexidine and superior to other herbal medicines in reducing the clinical signs of periodontal diseases. Conclusion: Aloe Vera is a herbal medicine with antibacterial and anti-inflammatory properties, proven through clinical and laboratory tests, able to act safely in the reduction of periodontal pathogens and, therefore, is effective as an adjunct in periodontal treatment.